The Collapse of the Ethics of the Public Sphere and its Educational Consequences - Kobylarek, Aleksander; Madej, Martyna; Birova, Jana (Journal of Education Culture and Society, 2022)
This article aims to present the ways in which the ethics of authority, including government, is collapsing in the contemporary world. The authors demonstrate what consequences numerous abuses and negligence can bring to education and the future. The article is based on reflections supported by actual research, which confirms the theses contained in it. Not only consequences are highlighted, but also ways in which they can be prevented. The most important aspect for the progress of science and the prevention of the depreciation of states is to stand firm against the abuses and appropriations committed by authority figures and to fight against “skimpiness” both in everyday life as well as in science. The current world picture does not promise a happy future. Humanity should strive for greater openness without allowing itself to be subjected to authorities whose actions contradict what they really are.